Ba–Al-decorated iron ore as bifunctional oxygen carrier and HCl sorbent for chemical looping combustion of syngas - Liu, Guicai (2021)
The simultaneous high-temperature HCl removal and chemical looping combustion (CLC) of syngas over barium-decorated oxygen carriers (OCs) was investigated. An iron ore was coated with a layer of sorbent (5 wt%) containing Ba and Al compounds (molar ratios Al:Ba = 0.5, 2.0, 4.5, 8.0, 12) and used for model syngas combustion at 800 °C. It was found that the synthesized materials can effectively remove HCl from the syngas. The HCl removal capacity increased with the Ba loading, and the HCl breakthrough capacity can reach 0.0345 mmol/g for the OC with Al:Ba = 0.5, resulting in the formation of BaCl₂. The conversion of Ba species into BaCl₂ was 17.3%. Besides the HCl sorption, the coating with Ba and Al compounds enhanced the activity of lattice oxygen and improved the reducibility of OCs during CLC due to the Ba–Fe composite formed on the OCs surface. Compared to the iron ore, the combustion efficiencies of the coated OC with Al:Ba = 4.5 for CO and H₂ increased from 62.2% and 87.2% to 99.6% and 95.9%, respectively. Through fluidized bed experiments and thermodynamic calculations, the feasibility of sorbent regeneration was demonstrated by treating OCs with a mixture of CO₂ and H₂O at 800–1000 °C. The HCl desorption rate increased with temperature and nearly complete sorbent regeneration (99.6%) could be achieved at 1000 °C. These findings demonstrate that Ba–Al-decorated iron ore can be used as bifunctional material in CLC process since it enables simultaneous high-temperature HCl removal and syngas combustion.